Pengaruh Pembelajaran Matematika Melalui Penerapan Model Pembelajaran Cooperative Learning Tipe Team Games Tournament (TGT) Terhadap Hasil Belajar Kelas IV - Wening, Nudya; Rahmawati, Noviana Dini; Jannah, Fitria Miftakhul (PGRI Kota Semarang, 2024)
SDN Pedurungan Kidul 01 The aim of this research is to provide an application in student learning to increase activeness, so that learning outcomes from the material provided to students can be conveyed well. In this learning, the model used is the TGT (Team Games Tournament) type cooperative learning model. The results of the research show that the application of the Team Games Tournament (TGT) type of Cooperative Learning learning model has had a significant impact on student learning outcomes in Mathematics in class V of SD Negeri Pedurungan Kidul 01. From the data collected, there has been a quite striking increase in the average The average student score after applying the TGT type Cooperative Learning concept. The pretest results showed that before using the TGT type Cooperative Learning model, the average student score was 65.7 with a total score of 1776. After implementing the TGT learning model in the post test period, there was a striking increase in the average student score to 85.03 with a total score of 2296.